AN INCIDENCE OF FOETAL, ASCITIS IN A A BUFFALO - K.N. Muraleedharan Nayar (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1995)
An incidence of Foetal aseitis in a buffalo is reported.